Analisis Sanksi Administratif OJK Terhadap PT Maseri Aset Manajemen dan Implikasinya Bagi Pasar Modal Indonesia - Nazwa Fadillah Cahya Ningrum Holak; Muhammad Robi; Novia Aisatul Oktavina; Nurlita Hidayatun Ni’mah; Emma Yunika Puspasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research analyzes the administrative sanctions given by the Financial Services Authority (OJK) to PT Maseri Aset Manajemen for governance violations, such as the absence of a physical office, business inactivity, not having professional employees, and not complying with OJK regulations. This research uses normative legal methods and a descriptive approach. The findings in this study show the importance of implementing Good Corporate Governance (GCG) and compliance with regulations. The research recommends increased stringent regulations and increased company compliance with OJK regulations